Representamen, Object, and Interpretant: A Peircean Approach to Traffic Signs in Pondok Indah - Inayah Zukhruftun (Semantik: Journal of Social, Media, Communication, and Journalism, 2025)
This research aims to analyze the semiotic meaning of traffic signs in Pondok Indah, Jakarta, using Charles Sanders Peirce’s triadic model of representamen, object, and interpretant. The study employed a qualitative descriptive method with data collected through observation, photographs, and Google Maps. A total of 21 traffic signs were examined. The findings reveal that each sign reflects Peirce’s semiotic elements and most function as legisigns regulated by Indonesian traffic law, while their interpretation depends on visual conventions and public awareness.